2007
DOI: 10.1029/2006pa001285
|View full text |Cite
|
Sign up to set email alerts
|

A paleomagnetic approach toward refining Holocene radiocarbon‐based chronologies: Paleoceanographic records from the north Iceland (MD99‐2269) and east Greenland (MD99‐2322) margins

Abstract: [1] We report the intercalibration of paleomagnetic secular variation (PSV) and radiocarbon dates of two expanded postglacial sediment cores from geographically proximal, but oceanographically and sedimentologically contrasting settings. The objective is to improve relative correlation and chronology over what can be achieved with either method alone. Core MD99-2269 was taken from the Húnaflóaáll Trough on the north Iceland shelf. Core MD99-2322 was collected from the Kangerlussuaq Trough on the east Greenland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 59 publications
6
118
0
Order By: Relevance
“…Our findings build on the results of quantitative XRD of the < 2 mm sediment fraction from core MD99-2269 (Table 1, Figure 2) , which has one of the best-dated Holocene records in the North Atlantic (Stoner et al, 2007). However, we agree with Alley (2003) that several cores from a region are required to fully substantiate a proxy record.…”
Section: Methods and Datamentioning
confidence: 54%
See 1 more Smart Citation
“…Our findings build on the results of quantitative XRD of the < 2 mm sediment fraction from core MD99-2269 (Table 1, Figure 2) , which has one of the best-dated Holocene records in the North Atlantic (Stoner et al, 2007). However, we agree with Alley (2003) that several cores from a region are required to fully substantiate a proxy record.…”
Section: Methods and Datamentioning
confidence: 54%
“…Figure 3B shows the median quartz wt.% distribution -this record is similar (r = 0.84) to the high-resolution 30 yr/sample quartz wt.% data from MD99-2269 (Figures 2 and 4A) . The fact that our multicore record captures most of the lower frequency variations in MD99-2269 ( Figure 4A) justifies the analysis of this core to provide a very high-resolution archive of Holocene environmental variability (eg, Andrews et al, 2003;Moros et al, 2006;Stoner et al, 2007) for an area affected by variations in the advection of Atlantic versus Arctic/Polar water masses (eg, Dickson et al, 1988). The time series of median quartz wt.% data is 'robust' in the sense that the estimate is not influenced by extreme values (Velleman and Hoaglin, 1981).…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to the NIS cores, where IP 25 and quartz wt% were well correlated (r 2 = 0.74 and 0.66 for MD99-2269 and JR51-GC35, respectively [Cabedo-Sanz et al, 2016]), their relationship is weaker for 2322 (r 2 = 0.44), likely indicating a change in provenance in one, or both, of the drift ice proxies. It is worth noting that the carbonate records in 2322 and MD99-2269 are virtually identical (Stoner et al, 2007). In contrast to the quartz and IP 25 data, the Fe grain inputs from SA42 and 43 decreased slightly over the last 1400 cal.…”
Section: Core 2322mentioning
confidence: 79%
“…It has a relatively high average sedimentation rate of 1 m/kyr for the upper 7 kyr to more than 5 m/kyr below this, and an excellent age model based on 20 calibrated radiocarbon dates and paleomagnetic data (Stoner et al, 2007;Jennings et al, 2011). Shipboard observations in 1991 and 1993 along the Geikie Plateau and in Kangerlussuaq Fjord indicated individual icebergs with supraglacial, englacial, or basal debris, which was especially evident for icebergs calved within the area of basalt outcrop, and aerial photographs showed that many of the glaciers on the Geikie Plateau had supraglacial sediment loads.…”
Section: Sediment Coresmentioning
confidence: 99%
See 1 more Smart Citation